The issues of environmental safety in the conditions of Eastern-Ukrainian war conflict - Babienko, V. V. (Journal of Education, Health and Sport, 2015)
Babienko V. V. The issues of environmental safety in the conditions of Eastern-Ukrainian war conflict. Journal of Education, Health and Sport. 2015;5(5):487-495. ISSN 2391-8306. DOI 10.5281/zenodo.18167 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A487-495 https://pbn.nauka.gov.pl/works/562687 http://dx.doi.org/10.5281/zenodo.18167 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.05.2015. Revised 28.05.2015. Accepted: 31.05.2015. The issues of environmental safety in the conditions of Eastern-Ukrainian war conflict Babienko V. V. Odessa National Medical University, Odessa, Ukraine SUMMARY The issues of environmental safety in the conditions of Eastern-Ukrainian war conflict Babienko V.V. Odessa National Medical University, Odessa, Ukraine The aim of the study was to assess the issues of environmental safety in the conditions of Eastern-Ukrainian war conflict. There was demonstrated that the risk of environmental contamination remains to be high in conflict areas. There is a great potential for long-term civilian health risks from the pollution generated by the war conflict in the Eastern Ukraine. The necessity to restore water infrastructure and access to safe drinking water in conflict areas and IDP shelters and to provide remediation means for elimination of long-term environmental risks related to the war conflict is discussed. Key words: environmental safety, environmental health, risk assessment, military medicine.